Preclinical evaluation of [13xLa]La-FAP-2286 as a novel theranostic agent for tumors expressing fibroblast activation protein - Ali Shirpour; Asghar Hadadi; Samaneh Zolghadri; Sara Vosoughi; Saeed Rajabifar (Scientific Reports)
Abstract In this study, a novel theranostic radiopharmaceutical, [13xLa]La-FAP-2286, for targeting Fibroblast Activation Protein (FAP)-positive tumors. The theranostic pair of 132La (half-life: 4.59 h, 42.1% β⁺) and 135La (half-life: 18.91 h, 100% EC) was produced via proton bombardment of natural barium in a 30 MeV cyclotron, achieving high radionuclidic purity (99.9%) and radiochemical purity (RCP > 99%). Stability tests revealed the RCP greater than 91% over 24 h in human serum and PBS buffer. Cellular studies confirmed high binding affinity (KD = 0.51 ± 0.12 nM) and effective internalization of [13xLa]La-FAP-2286 in FAP + tumor cells. Distribution coefficient (log D) measurements demonstrated high hydrophilicity of the complex with a value of − 3.21 ± 0.14. Imaging and biodistribution studies in tumor-bearing mice further confirmed tumor targeting, with significant uptake observed up to 48 h post-injection. These results suggest [13xLa]La-FAP-2286 can be considered a candidate for theranostic applications, offering both practical PET imaging and targeted Auger-electron therapy for cancer treatment.